Proceedings of the International Conference on Dublin Core and Metadata for e-Communities October 13-17, 2002, Florence, Italy - DC-2002 [AIB] (Proceedings e report, 2002)
DC-2002 marks the tenth in the ongoing series of International Dublin Core Workshops, and the second that includes a full program of tutorials and peer-reviewed conference papers. Interest in Dublin Core metadata has grown from a small collection of pioneering projects to adoption by governments and international organizations worldwide. The greatest challenge of the current phase of metadata development is bringing together the diversity of local conventions, domain specific requirements, and different encoding conventions such taht cross-domain interoperability can be achieved.